Using YouTube for Speaking in Online Learning: EFL Students’ Perception and Difficulties - khoiroh, shoburotin Annur (RETAIN, 2021)
Abstract This study aims to investigate student’s perception toward the use of YouTube in EFL speaking skill during online learning and to know student’s difficulties and how they solve them. This study involved 32 participants from non-English department students consisting 4 males and 28 females. To collect the data, the researcher uses open-ended questionnaire. To analyze the data, researcher used three steps, there are familiarizing and organizing, coding and reducing, and interpreting and representing the data. The result of the study shows that most of the participants have positive perception about the use of YouTube for speaking; as YouTube is helpful, affordable, and interesting platform to help them in some aspects of speaking. Some difficulties that students face while using YouTube are that they have internal and external difficulties. To solve the problem they use internet to browse, use YouTube features, and have discussion with friends and lecturer. Keywords: perception, YouTube, speaking skill, difficulties